2016
DOI: 10.3389/fphar.2016.00264
|View full text |Cite
|
Sign up to set email alerts
|

CB2 and GPR55 Receptors as Therapeutic Targets for Systemic Immune Dysregulation

Abstract: The endocannabinoid system (ECS) is involved in many physiological processes and has been suggested to play a critical role in the immune response and the central nervous system (CNS). Therefore, ECS modulation has potential therapeutic effects on immune dysfunctional disorders, such as sepsis and CNS injury-induced immunodeficiency syndrome (CIDS). In sepsis, excessive release of pro- and anti-inflammatory mediators results in multi-organ dysfunction, failure, and death. In CIDS, an acute CNS injury dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 84 publications
(112 reference statements)
1
24
0
2
Order By: Relevance
“…GPR55, which is strongly expressed in the nervous and immune systems as well as in other tissues, is a G-protein coupled receptor [93]. Activation of GPR55 increases the intracellular level of calcium ions [94].…”
Section: Gpr Receptorsmentioning
confidence: 99%
“…GPR55, which is strongly expressed in the nervous and immune systems as well as in other tissues, is a G-protein coupled receptor [93]. Activation of GPR55 increases the intracellular level of calcium ions [94].…”
Section: Gpr Receptorsmentioning
confidence: 99%
“…Administration of the CB1 receptor antagonist SR141716A in CB1 receptor-KO mice reduced anxiety-like behavior (Haller et al, 2002) while the CB1 receptor inverse agonist AM251 did not induce any significant alterations in anxiety-like behavior in CB1 receptor-KO mice (Thiemann et al, 2009). Our present findings that show an increase TH and decrease in α2-AR and β1-AR expression levels in CB1 receptor-KO mice may suggest involvement of a non-CB1 receptor and adrenergic receptors including vanilloid type 1 receptors (TRPV1) and GPR55 (Hong et al, 2009; Laricchiuta et al, 2013; Biernacki and Skrzydlewska, 2016;Marichal-Cancino et al, 2016; Zhou et al, 2016). It has been shown that eCBS can act to TRPV1 and GPR55 (Chavez et al, 2010; Hong et al, 2009; Laricchiuta et al, 2013; Biernacki and Skrzydlewska, 2016;Marichal-Cancino et al, 2016; Zhou et al, 2016).…”
Section: Discussionmentioning
confidence: 50%
“…Our present findings that show an increase TH and decrease in α2-AR and β1-AR expression levels in CB1 receptor-KO mice may suggest involvement of a non-CB1 receptor and adrenergic receptors including vanilloid type 1 receptors (TRPV1) and GPR55 (Hong et al, 2009; Laricchiuta et al, 2013; Biernacki and Skrzydlewska, 2016;Marichal-Cancino et al, 2016; Zhou et al, 2016). It has been shown that eCBS can act to TRPV1 and GPR55 (Chavez et al, 2010; Hong et al, 2009; Laricchiuta et al, 2013; Biernacki and Skrzydlewska, 2016;Marichal-Cancino et al, 2016; Zhou et al, 2016). Our electrophysiology data in WT mice confirmed findings from earlier studies in rats indicating that stimulation of α2-adrenoceptors enhances the excitability of mPFC pyramidal neurons coupled with an increase in cellular input resistance (Andrews and Lavin, 2006; Carr et al, 2007; Reyes et al, 2012; Cathel et al, 2014).…”
Section: Discussionmentioning
confidence: 50%
“…Cannabinoids have emerged as prominent modulators of diverse physiological and pathological processes. As such, efforts are underway to examine the efficacy of cannabinoid agonist and antagonists as therapeutic agents (McPartland et al, 2014 ; Russo, 2016 ; Toguri et al, 2016 ; Zhou et al, 2016 ). Cannabinoids primarily exert their effects through the cannabinoid receptors (CB1 and CB2); however, other receptors and molecular targets are now known to be important for their activity.…”
Section: Discussionmentioning
confidence: 99%